Lymphoepithelioma-like gastric carcinoma: A case report and review of the literature - Wang, Zhao-Hui (World J Gastroenterol, 2016)
Lymphoepithelioma-like gastric carcinoma is a rare type of gastric cancer characterized by a carcinoma with intense stromal lymphocytic infiltration. Although lymphocytic infiltration is closely associated with Epstein-Barr virus (EBV) infection, concomitant occurrence with differentiated adenocarcinoma is relatively rare. The clinical manifestations of lymphoepithelioma-like gastric carcinoma (including EBV-positive and -negative forms) are similar to those of gastric cancer, and the diagnosis is based on pathologic, histologic, and immunohistochemical findings. This report describes the case of a 55-year-old female patient who presented with a 10-year history of recurrent and worsening abdominal pain and melena that had been occurring for 2 mo. An ulcerative lesion was detected in the stomach by endoscopic examination, which raised suspicion of early gastric cancer. A subsequent preoperative endoscopic biopsy showed adenocarcinoma, but the postoperative pathologic, histologic, and immunohistochemical analyses of the resected specimen revealed a final diagnosis of lymphoepithelioma-like gastric carcinoma.